A novel strain of Leishmania braziliensis harbors not a toti- but a bunyavirus. - Alexei Yu Kostygov; Danyil Grybchuk; Senne Heeren; Evgeny S Gerasimov; Donnamae Klocek; Aditya Reddy; Jovana Sádlová; Lenka Pacáková; Alain Kohl; František Stejskal; Petr Volf; Jean-Claude Dujardin; et al. (PLoS Neglected Tropical Diseases)
Leishmania is a genus of the family Trypanosomatidae that unites obligatory parasitic flagellates causing a variety of vector-borne diseases collectively called leishmaniasis. The symptoms range from relatively innocuous skin lesions to complete failures of visceral organs. The disease is exacerbated if a parasite harbors Leishmania RNA viruses (LRVs) of the family Pseudototiviridae. Screening a novel isolate of L. braziliensis, we revealed that it possesses not a toti-, but a bunyavirus of the family Leishbuviridae. To the best of our knowledge, this is a very first discovery of a bunyavirus infecting a representative of the Leishmania subgenus Viannia. We suggest that these viruses may serve as potential factors of virulence in American leishmaniasis and encourage researchers to test leishmanial strains for the presence of not only LRVs, but also other RNA viruses.